(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Explanation models for the effectiveness of homeopathy are not supported by natural sciences and the aggregated evidence from clinical trials is unconvincing. From this standpoint, placebo effects seem the most obvious explanation for the therapeutic effects experienced in homeopathy. Still, many physicians continue to prescribe homeopathic treatments. OBJECTIVES Whether physicians who prescribe homeopathic treatments aim to achieve placebo effects or actually believe in specific effects is poorly understood. However, this distinction has important educational and ethical implications. Therefore, we aimed to describe the use of homeopathy among physicians working in outpatient care, factors associated with prescribing homeopathy, and the therapeutic intentions and attitudes involved. METHODS All physicians working in outpatient care in the Swiss Canton of Zurich in the year 2015 (n = 4072) were approached. Outcomes of the study were: association of prescribing homeopathy with medical specialties (odds ratios [OR] and 95% confidence intervals [95% CI] from multivariable logistic regression); intentions behind prescriptions (to induce specific or nonspecific/placebo effects); level of agreement with specific attitudes; and views towards homeopathy including explanatory models, rating of homeopathy’s evidence base, the endorsement of indications, and reimbursement of homeopathic treatment by statutory health insurance providers. RESULTS The participation rate was 38%, mean age 54 years, 61% male, and 40% specialised in general internal medicine. Homeopathy was prescribed at least once a year by 23% of the respondents. Medical specialisations associated with prescribing homeopathy were: no medical specialisation (OR 3.9; 95% CI 1.7-9.0), specialisation in paediatrics (OR 3.8 95% CI 1.8-8.0) and gynaecology/obstetrics (OR 3.1 95% CI 1.5-6.7). Among prescribers, only 50% clearly intended to induce specific homeopathic effects, only 27% strongly adhered to homeopathic prescription doctrines, and only 23% thought there was scientific evidence to prove homeopathy’s effectiveness. Seeing homeopathy as a way to induce placebo effects had the strongest endorsement among prescribers and non-prescribers of homeopathy (63% and 74% endorsement respectively). Reimbursement of homeopathic remedies by statutory health insurance was rejected by 61% of all respondents. CONCLUSION Medical specialties use homeopathy with significantly varying frequency and only half of the prescribers clearly intend to achieve specific effects. Moreover, the majority of prescribers acknowledge that effectiveness is unproven and give little importance to traditional principles behind homeopathy. Medical specialties and associated patient demands but also physicians’ openness towards placebo interventions may play a role in homeopathy prescriptions. Education should therefore address not only the evidence base of homeopathy, but also ethical dilemmas with placebo interventions.